Development of a Cued Pro- and Antisaccade Paradigm: An Indirect Measure to Explore Automatic Components of Sexual Interest. - Oberlader, Verena; Ettinger, Ulrich; Banse, Rainer; Schmidt, Alexander; Oberlader, Verena A; Schmidt, Alexander F (Archives of Sexual Behavior, 2017)
We developed a cued pro- and antisaccade paradigm (CPAP) to explore automatic components of sexual interest. Heterosexual participants (n = 32 women, n = 25 men) had to perform fast eye movements toward and away from sexually relevant or irrelevant stimuli across a congruent (i.e., prosaccade toward sexually relevant stimuli, antisaccade away from sexually irrelevant stimuli) and an incongruent condition (i.e., prosaccade toward sexually irrelevant stimuli, antisaccade away from sexually relevant stimuli). We hypothesized that pro- and antisaccade performance would be influenced by the sexual interest-specific relevance of the presented stimulus (i.e., nude female or male stimulus) and the instructed task (i.e., pro- or antisaccade) and, thus, differ meaningfully between conditions. Results for prosaccades toward sexually relevant stimuli in the congruent condition showed that error rates were lower and latencies were shorter compared with prosaccades toward sexually irrelevant stimuli in the incongruent condition, but only for male participants. In addition, error rates for antisaccades away from sexually irrelevant stimuli in the congruent condition were lower than for antisaccades away from sexually relevant stimuli in the incongruent condition, for both female and male participants. Latencies of antisaccades, however, did not differ between conditions. In comparison with established indirect sexual interest paradigms, the CPAP benefits from measuring highly automated processes less prone to deliberate control. To this end, the CPAP could be applied to explore the interplay of early automatic and deliberate components of sexual information processing.